Evaluation of Regional Cerebral Blood Flow Abnormalities Using Radionuclide Brain SPECT Imaging and Their Correlation with Symptoms in Childhood Autism Spectrum Disorder - Adnan, Sheikh Mohammad; Sultana, Nasreen; Alam, Mohammed Badrul; Bari, AKM Fazlul; Ananna, Fazana Rahman; Bailey, Shamsun Nahar; Ahmed, Tanvir; Bushra, Khansa Tabassum; Islam, Md Saiful (Bangladesh Journal of Medical Physics, 2025)
Autism Spectrum Disorder (ASD) is a complex neurodevelopmental condition that emerges early in life and remains challenging to diagnose accurately. This study evaluated regional cerebral blood flow abnormalities in 24 children with ASD, aged 3–12 years, using 99mTc ECD brain SPECT at the National Institute of Nuclear Medicine & Allied Sciences (NINMAS), Dhaka. Imaging data were analyzed with the Easy Z-Score Imaging System (eZIS) and correlated with Autism Diagnostic Checklist (ADCL) severity scores. Distinct hypoperfusion patterns were observed across severity levels. In mild ASD, hypoperfusion was consistently detected in the frontal lobe (100%), and in 70% of temporal and parietal regions. Low-moderate ASD cases exhibited widespread hypoperfusion across all brain regions, with universal involvement of the frontal and temporal lobes (100%). In high-moderate ASD, marked hypoperfusion was most pronounced in the parietal (100%) and frontal (83.3%) regions. Clinically, delayed speech was the most frequent symptom, followed by hyperactivity and cognitive impairment. Statistical analysis revealed a significant positive correlation between ADCL scores and Z-scores, indicating that greater perfusion deficits were associated with higher ASD severity. These findings demonstrate that brain SPECT not only identifies specific lobar perfusion deficits but also reflects symptom burden, underscoring its potential as a functional biomarker for diagnosis, monitoring, and guiding interventions in ASD. Ban. J. Med. Phys., Vol -16, Issue -2, 2025 : 65-72